Keeping the periodontium youthful: truth or myth? Strategy and tactical approaches in periodontology based on preventive, predictive, personalized medicine - I. A. Belenova; V. A. Mitronin; A. V. Sudareva; S. V. Startseva; M. S. Vasilyeva; E. A. Oleinik (LLC "Endo Press", 2022)
Relevance. The use of osteoplastic materials and hyaluronic acid in periodontology is extremely important for modern dentistry, since the predictive introduction of an osteoinductive drug and / or hyaluronic acid into the treatment protocol will allow simulating a state close to physiological, rejuvenating, and achieving the results of maximum restoration of periodontal structures.Aim. To experimentally confirm the possibility of maintaining the physiological state and rejuvenating the periodontium using osteoplastic materials and / or hyaluronic acid.Materials and methods. During the experiment, the dynamics of reparative osteogenesis in artificially reproduced defects of the jaw bones in rabbits was studied with the use of osteoplastic materials "Klipdent", "Bioplast-dent" or without the use of regeneration stimulants, as well as the morphogenesis of periodontal tissues when using hyaluronic acid. Results: the morphological studies carried out may indicate the acceleration of the regeneration processes in comparison with the normal course for 6-7 days.Conclusions. It has been experimentally proven that the preservation and prolongation of periodontal youth is possible. We consider it appropriate and important in the conditions of modern dentistry, provided that the correct clinical strategy and tactical methods are chosen. In particular, the improvement of the procedure for open curettage of the periodontal pocket by predictively introducing an osteoinductive drug and / or hyaluronic acid into the treatment protocol will significantly increase the effectiveness of therapeutic measures and restore the periodontal condition close to physiological.